Sistem Informasi Pengelola Bank ASI Berbasis Website (Studi Kasus: Posyandu Kelurahan Bantarsoka) - Tyas Pratama Puja Kusuma; Dania Gusmi Rahayu (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
The problem discussed in this study is designing a system that can be used as an ASI bank. The Posyandu in Bantarsoka Village is very concerned about the importance of breastfeeding for babies. A lot of babies who are not breast fed are a concern. On the other hand, many breastfeeding mothers also have excess breast milk. The absence of a system that accommodates information about ASI at the Posyandu in Bantarsoka Village makes the Posyandu less optimal in helping its residents overcome the problem of breastfeeding distribution. With current technological developments, the idea emerged to create an information system for ASI management, which later could be a solution to the problems. The ASI Bank Management System aims to provide a forum for mothers who have been excess breast fed to be able to donate their breast milk to babies who do not get their mother's milk intake. This study uses the Waterfall method which is carried out with a structured approach, starting from the system requirement's stages, analysis, design, coding, testing, and maintenance. The result of this research is an information system in the form on the ASI Bank website. With this system, it is hoped that it can help with the problem of breastfeeding distribution. The system created can properly manage and record breastfeeding ownership, who is the donors and recipients. By utilizing Internet technology, information dissemination can be accessed quickly and easily.